Relationship Between Immunoinflammation and Coronary Physiology Evaluated by Quantitative Flow Ratio in Patients With Coronary Artery Disease - Liu, Chengzhe; Yu, Zhiyao; Chen, Huaqiang; Wang, Jun; Liu, Wei; Zhou, Liping; Wang, Yueyi; Chen, Hu; Zhou, Huixin; Liu, Zhihao; Han, Jiapeng; Jiang, Hong; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between coronary physiology and immunoinflammation has not been investigated. We performed a retrospective study using quantitative flow fraction (QFR) to evaluate the interaction between immunoinflammatory biomarkers and coronary physiology. Methods: A total of 172 patients with CAD who underwent coronary arteriography (CAG) and QFR were continuously enrolled from May 2020 to February 2021. As a quantitative indicator of coronary physiology, QFR can reflect the functional severity of coronary artery stenosis. The target vessel measured by QFR was defined as that with the most severe lesions. Significant coronary anatomical stenosis was defined as 70% stenosis in the target vessel. Results: Compared with the QFR > 0.8 group, interleukin (IL)-6, IL-10, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ were increased and CD3+ and CD4+ T lymphocyte counts were decreased in the QFR ≤ 0.8 group. In addition, patients with DS ≤ 70% had higher IL-6, IL-10, and TNF-α levels and decreased CD3+ and CD4+ T lymphocyte counts than those with DS > 70%. Logistic regression analysis indicated IL-6 to be an independent predictor of significant coronary functional and anatomic stenosis (odds ratio, 1.125; 95% CI, 1.059–1.196; P<0.001). Receiver operating characteristic (ROC) analyses showed that IL-6 > 6.36 was predictive of QFR ≤ 0.8 of the target vessel. The combination of IL-6, IL-10 and CD4 improved the value for predicting QFR ≤ 0.8 of the target vessel (AUC, 0.737; 95% CI, 1.059–1.196). Conclusion: Among immunoinflammatory biomarkers, IL-6 was independently associated with a higher risk of QFR ≤ 0.8 of the target vessel. The combination of immunoinflammatory biomarkers was highly predictive of significant coronary functional and anatomic stenosis.